Pesan Nonverbal pada Web Series “Mengakhiri Cinta dalam 3 Episode” - Naufal Asyrof Rizky; Nani Kurniasari (UNIVERSITAS KALBIS, 2022)
As the rapid progress in cyberspace or we are familiar with the internet, now filmmakers no longer rely on television and the mainstream media to showcase work. As in this study which discusses a series of shows on social networks that can be enjoyed anywhere and anytime, commonly referred to as